Irrigation management research in Sri Lanka: A review of selected literature. Occasional paper. Occasional paper - Merrey, Douglas J.; Rao, P.S.; Martin, E. (International Irrigation Management Institute, 1988)
This paper reviews literature in four topic areas of relevance to Sri Lanka: system operations and performance, organization and management of irrigation systems, rehabilitation and modernization of irrigation systems, and resource generation and mobilization. A review on crop diversification issues is included as an Appendix. Most of the literature reviewed concentrates on large irrigation schemes and focusses on literature published since 1978. The paper attempts to identify, for each of the four topics, the progress made and lessons learned, and to suggest research questions that ought to be addressed.